Excessively up at the International Labour Organisation : Notes on « Note on the Proceedings TMITI/2007/10 » - Hertz, Ellen (My University, 2010)
This paper was written for a collection of essays in honor of U.C. Berkeley professor Laura Nader, author of the famous phrase “studying up”. Nader’s concept of “studying up” provides us with a highly focused lens for examining the workings of power. If we turn this lens on the ordinary proceedings of a minor meeting at the International Labour Organisation in Geneva, a meeting that I had the privilege of attending as a representative of the Swiss government, one finds that power of the sort that Nader seeks to analyze is not present at the ILO. Instead, one finds a complex circulation of ideals, terms and documents that must be studied in a perspective that I have labeled “the social life of terms”. This circulation does indeed involve “upness”: high levels of generality that allow for certain forms of compromise and, more importantly, loftiness of principle that can then be siphoned back into national and local settings. The price for this “height”, however, is a feeling of enormous distance between the grandeur of the mission of international organizations such as the ILO and the reality of their impact “on the ground”. “Studying up” in the 21st century will involve following the circulation of such loftiness, and repeatedly taking the measure of its distance from problems “on the ground”, without forgetting to ask whose interests are advanced when, where and why.
Keywords: Studying up; International Labour Organization; International organizations; Labor Rights; Electronic manufacturing; Anthropology of bureaucracy